Pengaruh Latihan Shadow Terhadap Kelincahan Footwork Siswa Ekstrakulikuler Bulutangkis Sekolah Menengah Atas Katolik ST. Albertus Malang - Byan Bagas Bramudya; Sapto Adi; Ardhiyanti Puspita Ratna (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
As a fast-paced sport, badminton necessitates quick reflexes and agility on the court in order to hold and drop the shuttlecock into the opposing court. The goal of this research was to see how students in the badminton club at St. Albertus Catholic High School in Malang responded to shadow training to improve their agility. The research employed a pre-experimental strategy, specifically, a one-group pre-post test layout. There were two meetings per week for a total of eight weeks during this study. In order to get in shape, try this 6-point shadow training program. The shadow test was used as the instrument to gauge agility in this research. The t-test for paired samples was used to analyze the data in this study. The significance level of 0.000 for the t-test hypothesis test with paired samples t-test analysis is lower than the conventional threshold of 0.05. As a result, we can conclude that H1 is true and H0 is false. Students participating in badminton as an extracurricular activity at St. Albertus Catholic High School in Malang found that shadow training significantly improved their agility.